The Effect of Compensation and Work Environment on Employee Loyalty - Anika Riana; Hanifah Yasin (Proceeding International Seminar of Islamic Studies, 2019)
The purpose of this study is to determine the influence of the Work Environment on Kerj a Loyaltyin PT. Arpeni Pratama Ocean Line Medan. To know the influence Compensation and Work Environment for Work Loyalty to PT. Arpeni Pratama Ocean Line Medan Compensation is intended as a reward for the company's services (rewards) dueto the sacrifice of time, time, energy and thoughts that have been given by employees to the company. The work environment is everything related to the physical aspect and the psychic aspect that will directly or indirectly affect thedevice. In accordance with the problems posed in the study, the purpose of this study is to determine the effect of Compensation on Work Loyalty in PT. Arpeni Pratama Ocean Line Medan. The analysis technique used inthis research is quantitative data analysis, which is to test and analyze data by calculating numbers and then drawing conclusions from the test with product moment correlation test tools and multiple correlations but in practice the processing of this research data is not processed manually, but using  SPSS statistical software.